Wind energy : renewable energy and the environment - Nelson, Vaughn; Starcher, Kenneth (Boca Raton, FL : CRC Press, 2019)
This book explores the wind industry from its inception in the 1970s to today; presents the design, aerodynamics, operation, control, applications, and different types of wind turbines; and provides ample reasons to shift from fossil fuels to renewable energy. It also discusses the political and economic factors regarding the adoption of wind as an energy source. It covers the characteristics of wind, such as shear, power potential, and turbulence, and discusses the measurement and siting of individual wind turbines and wind farms. This new edition is fully updated throughout, and adds new material on wind forecasting, offshore wind, decommissioning and repowering wind farms, and more.
OCLC-licensed vendor bibliographic record.
Keywords: Wind power; Wind power plants; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Energy